Lower Extremity Pain and Pitching Kinematics and Kinetics in Collegiate Softball Pitchers - Oliver, Gretchen D.; Friesen, Kenzie B.; Barfield, Jeff W.; Giordano, Kevin A.; Bordelon, Nicole M.; Anz, Adam W.; Goodlett, Michael D.; Andrews, James R. (International Journal of Sports Medicine, 2020)
The primary aims of the study were (1) to examine kinematics and kinetics of those pitching with and without lower extremity pain in collegiate softball pitchers, and (2) to determine if there was an association between the lower extremity pain and lower extremity kinematics, trunk kinematics, and shoulder kinetics in collegiate softball pitchers. Thirty-seven NCAA Division I female collegiate softball pitchers (19.8±1.3 yrs,173.7±7.7 cm, 79.0±12.4 kg) participated. Participants were divided into two groups, those who were currently experiencing lower extremity pain and those who were not. Participants threw three rise ball pitches. Kinematic data were collected at 100 Hz using an electromagnetic tracking system. Mann-Whitney U tests revealed no significant kinematic or kinetic differences between pitchers with and without lower extremity pain. Additionally, there were no significant correlations between pain and recorded kinematic and kinetic variables. Considering there were no biomechanical differences observed between pitchers, coaches and athletic trainers should take caution with athlete assessment since athletes may not display altered biomechanics. Further examination into the duration and degree of pain is needed in an attempt to fully understand the implication of pain and pitching mechanics.
Keywords: distal mobility; kinetic chain; proximal stability; windmill softball pitching